Child and Adolescent Mental Health 2017
DOI: 10.5772/67578
|View full text |Cite
|
Sign up to set email alerts
|

Draw, Write, Speak, Play: The Role of Projection in Diagnosis and Therapy of Children and Adolescents

Abstract: In this chapter, I will (1) review the concept and function of projective mechanisms on a psychodynamic basis. In this section, I will outline the relation of projection to the unconscious, its use in innerpsychic dynamics, and the underlying mechanisms for its use in psychotherapy like creativity, imagination, and symbolization; (2) give an overview over the use of projective methods for testing and diagnosis in the psychological sciences; and (3) exemplify the use of projective methods in diagnostics and psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Previous theoreticians showed that doodles also often hide deeper meanings and are capable of unfolding the subconscious (Feuer, 2000;Maurer, 2017). Spontaneous squiggles have been analyzed because Vass (2011) as revealing the appearance of the subconscious.…”
Section: Subconscious Activation and Self-conscious Integration In At...mentioning
confidence: 99%
“…Previous theoreticians showed that doodles also often hide deeper meanings and are capable of unfolding the subconscious (Feuer, 2000;Maurer, 2017). Spontaneous squiggles have been analyzed because Vass (2011) as revealing the appearance of the subconscious.…”
Section: Subconscious Activation and Self-conscious Integration In At...mentioning
confidence: 99%
“…Different researchers (Vágnerová, 2017;Cohen et al, 1994;Leigh Neale, 1994;Maurer, 2017;Shukla et al, 2012) have dealt with creativity as a diagnostic tool for psychological diagnostics in both children and adults.…”
Section: Creativity and Deaf Or Hard Of Hearingmentioning
confidence: 99%